Family law arbitration : practice and precedents - Sheridan, Dennis; Kingston, Suzanne (London : Bloomsbury Professional, 2022)
Family Law Arbitration is a guide to arbitration in family matters both financial and in respect of children. It gives practitioners and lay individuals an understanding of family law arbitration, how it works in family matters and what can be expected when an arbitration proceeds, showing both the lawyers involved and the client all they need to know in terms of practice and procedure. There have been a number of developments since publication of the second edition in 2017 including numerous cases and revised practice guidance over the years which are referenced in the book. Family Law Arbitration is essential reading for the judiciary, legal practitioners, local authorities, academics and students in the UK. It is also of interest to the legal profession, academics and students internationally as it provides a comparison of Family Law Arbitration in England and Wales with the regime in other jurisdictions as well as an understanding as to its advancement and development and why Arbitration in England and Wales can assist in international family law matters..
Part I - Family law arbitration in practice --1. Introduction --2. Procedure --3. Guidance --Part II - Appendices --1. Legislation, rules and practice guidance --2. Forms, precedents and standard orders --3. Case studies --4. Remote Arbitrations --5. Articles --6. Cases.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Arbitration -- Mediation -- United Kingdom; Family law -- United Kingdom; Law; Arbitration and award; Domestic relations; Wales; England